A percepção dos estudantes do ensino médio, quanto a importância das políticas públicas - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
High school students from Alenquer, PA, are investigated regarding the importance and impact of public policies on their lives and the local community. The main objective is to analyze how these students understand the importance and impact of such policies in their lives and the local community. The research also discusses youth concepts and examines public policies directed at young people in Brazil over the past two decades. A descriptive and exploratory case study methodology was employed, utilizing questionnaires to collect data from students. Results indicate that most young people have a basic or superficial understanding of the topic and limited participation in citizenship activities or debates, highlighting a gap in political engagement. Nonetheless, students recognize the significance of public policies in improving essential services such as health and education and ensuring fundamental rights. The findings underscore the need for more inclusive political education and initiatives that promote greater awareness and active participation among youth in political processes. The study concludes that the youth play a critical transformative role and that incorporating their perspectives in the planning and implementation of public policies is essential for building a more democratic and equitable society.
Keywords: Políticas Públicas; Participação; Juvenil; Ensino Médio; CNPQ::CIÊNCIAS HUMANAS